Floristic zoning of high-mountain landscapes of the Central and North-Eastern Caucasus - M A. Astamirova; M. A. Taysumov; A. S. Abdurzakova; R. S. Magomadova; F. S. Omarkhadzhieva (Юг России: экология, развитие, 2023)
Aim. To carry out floristic zoning of high-mountain landscapes of the Central and North-Eastern Caucasus.Material and Methods. A list of obligate petrophytes was compiled based on the results of processing the authors' own field collections and taking into account information from floristic reports and determinants. The assessment of the similarity of species composition of the flora of the high-mountain landscapes of the Central and North-Eastern Caucasus was carried out according to the Jaccard and S0rensen-Chekanovskiy coefficients.Results. Based on the analysis of similarity of floristic lists, the geographical boundaries were corrected and three floristic regions of petrophilic high-mountain flora were identified.Conclusion. This analysis of the similarity of the petrophilic floras of the high-mountain landscapes of the Central and North-Eastern Caucasus has shown that it is necessary to correct the boundaries of the existing scheme of floristic zoning, since the similarity of coefficients of floristic lists indicates the possibility of combining a number of areas based on a small degree of difference between their floras and the presence of a significant number of species whose ranges are unifying.